A central approach to splenorenal shunt in pediatric living donor liver transplantation. (29th June 2015) - Uchida, Hajime; Fukuda, Akinari; Masatoshi, Matsunami; Sasaki, Kengo; Shigeta, Takanobu; Kanazawa, Hiroyuki; Nakazawa, Atsuko; Miyazaki, Osamu; Nosaka, Shunsuke; Sakamoto, Seisuke; Kasahara, Mureo
Abstract The management of LSRS is a crucial problem to ensure a sufficient PV flow during pediatric LT. Although several techniques have been indicated to solve this problem, a more appropriate approach to LSRS is still needed in pediatric LT. We herein present a modified surgical approach to the ligation of LSRS via the left side of the IVC for a nine‐month‐old boy with severe portal hypertension and a history of Kasai portoenterostomy. LSRS was identified and exposed through the left side of the IVC and the dorsal surface of the pancreas from the superior side of the body of the pancreas. The post‐operative course was uneventful with an excellent PV flow. The central approach for the ligation of LSRS is worth considering as an alternative procedure for a patient with collateral vessels and a history of multiple laparotomies.